Autonomy at Work: The Perspective of a Group of Brazilian Skilled Workers. Issue 4 (1st October 2016) - Lopes, Ana Luiza Szuchmacher Verissimo; Garibaldi de Hilal, Adriana Victoria
ABSTRACT: This study investigated the variety of understandings of autonomy at work from the perspective of a group of Brazilian skilled workers. The research method used was phenomenography, a qualitative and interpretative research approach. The results constitute a system that provides a comprehensive description of autonomy based on the variation in perspectives across the interviewees. The outcomes suggest that an overall sense of authorship regarding a broad range of decisions is inherent to the experience of autonomy. The findings also suggest that an expanded conception of autonomy includes not only professional but also personal and lifestyle aspects.